AN OVERVIEW OF DROWNING IN NEW ZEALAND AND ASSOCIATED RESEARCH EFFORTS. (7th October 2012) - Webb, S; Brunt, A
Abstract : Background: Water Safety New Zealand (WSNZ) is New Zealand's national organisation responsible for water safety education, awareness and prevention. It represents 35 organisations within New Zealand that have an interest in water safety. Drowning affects all New Zealanders irrespective of age, ethnicity, gender or social economic status. It is consistently the third highest cause of unintentional death in New Zealand, surpassed only by road vehicle crashes and accidental falls. WSNZ and its members have achieved considerable success since its inception in 1949. Over the last 29 years a 60% reduction in drowning has occurred since a record high in 1985 of 215 and a record low of 87 in 2010. Currently on average (last 5 years) 105 New Zealanders die per annum from drowning. Aim/Purpose: In order to reduce drowning in New Zealand WSNZ established a Research Advisory Group (RAG) in 2008/2009. This RAG produced a Research Strategy that contains the national research objectives and outcomes for New Zealand over the next 3–4 years. Methods: In order to establish the Strategy a critical review of New Zealand and international research published since 1990 was completed. The review investigated the RAG's main areas of inquiry, focusing specifically on published, unpublished and in-progress research. Results: To date the following has been completed: Literature review National Strategy Doctoral scholarship programme established Report on Canyoning in New Zealand Research on behavioural analysis of human characteristics following sudden water immersion Contribution to the Field: An overarching strategy that has delivered key pieces of research for the sector. Water Safety New Zealand (WSNZ), PO BOX 10126, Wellington 6143, New Zealand Phone: +64 4 801:9600 Email: alex@watersafety.org.nz Website: http://www.watersafety.org.nz